2018
DOI: 10.24264/icams-2018.ix.1
|View full text |Cite
|
Sign up to set email alerts
|

In-situ Modified Antimony-Film Glassy Carbon Electrode for Metal Trace Analysis

Abstract: Glassy carbon electrodes (GCE) have been extensively employed for the determination of trace amounts of heavy metals. Lately, modifications of GCE are currently being sought. One way of obtaining better analytical performance compared to GCE is the employment of an in situ prepared antimony-film glassy carbon electrode (SbFE). This combination is especially attractive in anodic stripping voltammetry technique which uses square wave excitation signal. This work will report on the optimization of the in situ pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The deposition of Sb and the analytes for partial method validation was performed at -1.1 V in the case of the 0.01 M HCl solution and at -1.4 V for the acetate buffer solution, with an accumulation time (t acc ) of 60 s in both cases. The accumulation potential for the 0.01 M HCl solution was selected based on our previous study, which revealed the best electroanalytical performance when accumulation potential optimization was performed at -1.0, -1.1, and -1.2 V. 34 An accumulation potential of -1.4 V was selected based on the voltammograms measured (presented below), where hydrogen evolution was not intensive at that accumulation potential and the three analytes were accumulated on the electrode surface from the 0.1 M acetate buffer solution with and without the addition of 0.5 mg/L Sb(III). The cleaning and deposition steps were performed under continuous stirring (300 rpm).…”
Section: Methodsmentioning
confidence: 99%
“…The deposition of Sb and the analytes for partial method validation was performed at -1.1 V in the case of the 0.01 M HCl solution and at -1.4 V for the acetate buffer solution, with an accumulation time (t acc ) of 60 s in both cases. The accumulation potential for the 0.01 M HCl solution was selected based on our previous study, which revealed the best electroanalytical performance when accumulation potential optimization was performed at -1.0, -1.1, and -1.2 V. 34 An accumulation potential of -1.4 V was selected based on the voltammograms measured (presented below), where hydrogen evolution was not intensive at that accumulation potential and the three analytes were accumulated on the electrode surface from the 0.1 M acetate buffer solution with and without the addition of 0.5 mg/L Sb(III). The cleaning and deposition steps were performed under continuous stirring (300 rpm).…”
Section: Methodsmentioning
confidence: 99%
“…197,248 Trace heavy metal analysis has been performed either with just BiFEs 247,248,252,253,[255][256][257]260 or with electrodes modified with a Bi-film combined with other materials and/or compounds, including with different NMs, 25,50,83,181,256 Nafion and GO, 40,83,233,235,250 as well as doping of the Bi-films with boron or indium. 245,259 Various other metals, including Sb, [261][262][263][264] Cu, [265][266][267] Au, 268 Pb, 269 and Hg, 260 have also been electrodeposited on different types of electrodes. Moreover, complexing agents such as 8-hydroxyquinoline, 251 nioxime, 265 and cupferron 269 have been added during the in situ Bi-, Pb-, and Cu-film modification of GCEs.…”
Section: Film-forming Substances As Electrode Modifiersmentioning
confidence: 99%
“…7,12,243 In the last five years, the research was focused on preparing two main types of film electrodes, i.e. , metallic- 25,40,50,83,181,197,233,235,245–273 and polymeric-film electrodes. 77,91,94,95,141,210,217,220,223–230,274–276 However, the combination of metallic (Bi) and polymer films ( i.e.…”
Section: Film-forming Substances As Electrode Modifiersmentioning
confidence: 99%